CT-Guided Stellate Ganglion Pulsed Radiofrequency Stimulation for Facial and Upper Limb Postherpetic Neuralgia - Ding, Yuanyuan; Yao, Peng; Li, Hongxi; Han, Zhenkai; Wang, Shimeng; Hong, Tao; Zhao, Guangyi (Frontiers in Neuroscience, 2019)
Objective: Postherpetic neuralgia (PHN) is the most common complication of herpes zoster, manifesting as a persistent, spontaneous, knife-like pain or paroxysmal burning that seriously affects a patient’s quality of life. An effective treatment of PHN is lacking. This retrospective study examined the efficacy and safety of stellate ganglion (SG) pulsed radiofrequency (PRF) on facial and upper limb PHN. Methods: Eighty-four patients with PHN on the face or upper limbs were enrolled for the study. Patients were randomly divided into 2 surgical groups according to the order of enrollment; one group underwent SG block (SG-B group, n=42) and the other underwent SG pulsed radiofrequency (SG-P group, n=42). After surgery, patients were followed at 1 week, 2 weeks, 1 month, 3 months and 6 months. Observation at each follow-up included basic patient characteristics, visual analogue scale (VAS), quality of life (QOL) using Physical Component Summary (PCS) and Mental Component Summary (MCS) to assess, total effective rate, complications and side effects. Results: Compared with preoperative values, VAS decreased in both groups after surgery (P<0.05). In the SG-B group, VAS increased after 1 month, while in the SG-P group, VAS gradually decreased at later follow-up time points. VAS decreased more significantly in the SG-P group after 1 month (P < 0.05). PCS and MCS increased in both groups after the operation, and the difference was significant compared with preoperative values (P < 0.05). The total effective rates of the SG-B and SG-P groups were 64.3% and 83.3%, respectively. The total effective rate of the SG-P group was higher than that of the SG-B group (P<0.05). The incidence of complications and side effects in the SG-B group was higher than that in the SG-P group (P<0.05). Conclusions: SG pulsed radiofrequency treatment of facial and upper limb PHN is safe and effective. It is a treatment method worth promoting.